PENGARUH PROFITABILITAS, SOLVABILITAS DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Suriani Ginting (Universitas Methodist Indonesia, 2018)
This study aims to determine and analyze the effect of profitability, solvency, and firm size on audit delay in manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2016. The research data were taken from www.idx.co.id. The population in this was 144 manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2016. The sample selection technique used purposive sampling technique. Total samples obtained in this study were 69 companies. The data testing method used a multiple linear regression analysis. The results showed that simultaneously profitability (ROA), solvency (DAR) and company size had a significant effect on Audit Delay. Partially the solvency and the company size have a significant effect on audit delay, but profitability (ROA) does not affect audit delay. Adjusted R Square value is 0.072 which means 7.2% audit delay can be explained by the independent variables in this study.